Isotretinoin and adverse neuropsychiatric outcomes: retrospective cohort study using routine data - Paljarvi, T; McPherson, T; Luciano, S; Herttua, K; Fazel, S (Wiley, 2022)
Background Severe neuropsychiatric outcomes have been reported in individuals exposed to isotretinoin, but the evidence is inconclusive and complicated by several methodological limitations. Objectives To establish and quantify the association between isotretinoin use for acne and 1-year incident neuropsychiatric adverse outcomes. Methods A propensity score-matched cohort study of electronic medical records between the years 2013 and 2019 with patients followed up for 1 year after their index dispensed prescription was conducted. The database included over 12 million patients aged 12–27 years. We analysed data for individuals with acne in this age range with a dispensed prescription for isotretinoin or a control prescription. Outcomes included diagnoses of any incident sleep or mental health disorder, or nonfatal self-harm within 1 year of the index prescription. Results We included 30 866 patients prescribed isotretinoin for their acne, 44 748 prescribed oral antibiotics, 108 367 prescribed topical anti-acne agents and 78 666 patients with acne but without an anti-acne prescription. After propensity score matching for baseline confounders, the odds ratio (OR) for any incident neuropsychiatric outcomes in patients with acne exposed to isotretinoin was 0·80 [95% confidence interval (CI) 0·74–0·87] compared with those on oral antibiotics; 0·94 (95% CI 0·87–1·02) compared with those using topical anti-acne medicines; and 1·06 (95% CI 0·97–1·16) compared with those without a prescription for anti-acne medicines. Patients exposed to isotretinoin experienced significantly more incident physical symptoms than patients in any of the three comparison cohorts. Conclusions Isotretinoin was not independently associated with excess adverse neuropsychiatric outcomes at the population level. When monitoring potential adverse outcomes during isotretinoin treatment, clinicians should also consider the high mental health burden associated with treatment-resistant acne and the potential contribution of physical side-effects of prescribed medication on mental health. What is already known about this topic? Severe neuropsychiatric outcomes have been reported in individuals exposed to isotretinoin, but the evidence is inconclusive and complicated by several methodological limitations. The neuropsychiatric risks potentially associated with isotretinoin treatment are an ongoing concern to clinicians and individuals with treatment-resistant acne. Current isotretinoin prescribing guidelines recommend close monitoring for adverse mental health outcomes during isotretinoin treatment. What does this study add? After controlling for various potential sources of bias, isotretinoin was associated with a reduced incidence of adverse psychiatric outcomes (odds ratio 0·80, 95% confidence interval 0·74–0·87) compared with oral antibiotics. Isotretinoin appeared to reduce the excess psychiatric risk associated with treatment-resistant moderate-to-severe acne. In monitoring potential adverse outcomes during isotretinoin treatment, clinicians should also consider the high mental health burden associated with treatment-resistant acne and the potential contribution of physical side-effects of the prescribed medication on mental health.